The effectiveness of a counseling program based on multi-modal therapy theory in managing anger among a sample of patients with arterial hypertension, a quasi-experimental study in the city of Lattakia.: The relationship between anger and strategies for dealing with psychological stress among a sample of patients with arterial hypertension (a comparative field study between patients and non-patients in Lattakia Governorate) (Journal of Hama University, 2025)
This paper aims to study the differences between a sample of primary hypertension patients and a sample of non- patients, taking into account the variables of anger (both as case and trait), and ways of dealing with stress focused on emotion. These variables were measured using the research tools of measures of anger, and the scale of ways of dealing with stress. Also, the study used the descriptive- comparative method to investigate the hypotheses that there are differences between both samples in all variables of the study studied.
Keywords: primary hypertension, anger traits, ways of dealing with stress.